Effect of Amount of Aluminum on the Performance of Si-Al Codeposited Anodes for Lithium Batteries - Patil, Vaishali; ArunPatil; Yoon, Seok-Jin; Choi, Ji-Won (AMER SCIENTIFIC PUBLISHERS, 2015)
Silicon is considered one of the most promising anode materials for high-performance Li-ion batteries due to its 4000 mAh/g theoretical specific capacity, relative abundance, low cost, and environmental benignity. However, silicon experiences a dramatic volume change (similar to 300%) during full charge/discharge cycling, leading to severe capacity decay and poor cycling stability. Here, we report Si-Al codeposited anode material for Li-ion batteries. The Si-Al thin films were deposited by co-deposition from Si and Al target on nickel substrate. The composition of Si and Al in the film is estimated by energy-dispersive spectroscopy. The XRD and SEM analysis revealed that the Si Al thin films were amorphous in structure. The electrochemical performance of the Si Al thin film as anode material for lithium ion battery was investigated by the charge/discharge tests. Galvanostatic half-cell electrochemical measurements were conducted in between 0 mV to 2 V using a Li counter electrode, demonstrating that the Al rich Si Al thin film achieved a good cycleability up to 100 cycles with a high capacity retention. Si-Al sample having 11.04% Al shows capacity 825 mAh/g over the 100 cycles.
Keywords: LI-ION BATTERIES; RECHARGEABLE BATTERIES; ELECTROCHEMICAL CHARACTERISTICS; HIGH-CAPACITY; ALLOYS; FILMS; ELECTRODES